2015
DOI: 10.1093/jme/tjv064
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Survey for Sand Fly Fauna in Imamoglu Province (Cutaneous Leishmaniasis Endemic Region) of Adana, Turkey

Abstract: Leishmaniasis, presenting in two clinical forms, cutaneous and visceral in Turkey, is widespread in most of the countries in the Mediterranean Basin. An average of 10 to 13% of cases are reported from Adana every year. This paper presents the results of an entomological survey in an endemic focus of cutaneous leishmaniasis in Imamoglu province of Adana in Turkey.We collected 654 sand fly specimen using 100 light traps in 20 nights in August 2013 and July 2014. Several keys and previous drawings were used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Nevertheless, the combination of these two methodologies allows an extensive and comprehensive study of infection rates and characterization of Leishmania parasites as reported in Italy, Turkey and Israel [ 47 49 ]. Mean infection rates found by dissection in the present work are similar to some studies carried out in Spain [ 4 , 50 – 53 ] but higher than reported in other countries [ 26 , 47 , 48 , 54 ]. The infection rates found in this study showed different pattern during the three surveys, possibly due to differences observed in the number of sand fly captures.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the combination of these two methodologies allows an extensive and comprehensive study of infection rates and characterization of Leishmania parasites as reported in Italy, Turkey and Israel [ 47 49 ]. Mean infection rates found by dissection in the present work are similar to some studies carried out in Spain [ 4 , 50 – 53 ] but higher than reported in other countries [ 26 , 47 , 48 , 54 ]. The infection rates found in this study showed different pattern during the three surveys, possibly due to differences observed in the number of sand fly captures.…”
Section: Discussionsupporting
confidence: 90%
“…infection rates in sand flies analysed individually ranged between 0% and 1.96% (Table 3) (Bolukbas et al, 2016; Özbel et al, 2016; Svobodová et al, 2009; Töz et al, 2009). Similarly, minimum infection rates in pooled sand fly samples were between 0.63% and 5.17% (Demir & Karakuş, 2015; Karakuş, Arserim, et al, 2019; Karakuş et al, 2017; Kavur et al, 2018; Kavur et al, 2015; Özbel et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…According to the previous entomological survey results18 probable sand fly species have been identified in Turkey 5,8,28,29 . Five of them (P. papatasi, P. sergenti, P. neglectus/syriacus, P. perfiliewiand P. tobbi) were detected in our study area 8,30 . Our results are associated with the results of previous studies in that there is a relationship between environmental factors and presence of vector species.…”
Section: Discussionmentioning
confidence: 99%
“…According to the various entomological survey results;six Phlebotomus species (P. tobbi, P. syriacus, P. perfiliewi, P. papatasi, P. sergenti and P. simici) exist in Adana. In addition P. tobbi was found to be dominant species in Adana and Cukurova Region [5][6][7][8][9] .…”
Section: P Tobbi Is the Proven Vector Of CL Caused Bymentioning
confidence: 99%